Programming in COBOL - Lancaster, G. T. (Library of computer education., 1972)
Programming in COBOL is a simple yet concise how-to book that teaches the programming language in a short yet effective step-by-step manner, which can be easily understood by anyone with sufficient knowledge in information technology.